Comment on: "Isothermal nature of the B2–B19′ martensitic transformation in a Ti–51.2 Ni (at.%) alloy". (15th March 2015) - Pelegrina, J.L.; Yawny, A.; Olbricht, J.
Abstract : Fukuda et al. published a paper (Scripta Mater. 68 (2013) 984–987) in which they claimed to be able to determine the isothermal nature of the martensitic transformation in a Ti–Ni alloy. They analyzed the evolution of electrical resistance during isothermal holding stages and concluded that the variations were a consequence of the isothermal transition between austenite and martensite. In the following we will demonstrate that the discussed data do not allow the interpretation presented and that the isothermal nature is not proved.